ANALISIS PENYAMBUNGAN LAS GTAW(GAS TUNGSTEN ARC WELDING)/TIG MENGGUNAKAN MESIN LAS SMAW (SHIELDED METAL ARC WELDING) DENGAN DYE PENETRANT TEST - Firdiansyah Candra; Sugiyarto Sugiyarto; Erwanto Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Welding itself is a technique of joining metal with some of the parent metal and filler metal, which can be used as an addition metal or not and produces a continuous metal. Gas Tungsten Arc Welding (GTAW) or often also called Tungsten Inert Gas (TIG) is used. one of the forms of electric arc welding (Arc Welding) that uses an inert gas as a shield with tungsten or tungsten as the electrode, SMAW welding machine is a welding machine that uses DC, AC, or DC/AC currents. The purpose of this final project is to find out whether GTAW welding can be done using a SMAW welding machine because the SMAW welding machine has an easy machine setting process and relatively affordable machine prices with clean results from slag and can also weld thin plates with maximum results using welding. GTAW. The results of this study are information about the success or failure of the GTAW welding process using a SMAW welding machine. The amperes used are 43,46,49,52,55,58 and 61 as well as testing the welding results using dye penetrant. The conclusion obtained in this study is that GTAW welding can be done using a SMAW welding machine. And it was also found that the second welding using alternating welding method I was better than welding 1 by unidirectional welding using I seam.